The effect of the time parents spend with children on children's well-being - Li, Dongxu; Guo, Xi (Frontiers in Psychology, 2023)
Background The time spent with parents is a crucial factor in the growth of children, and children's well-being is an important indicator of their mental health. Methods To promote the children's well-being, this study, which is relying on the data from the 2017 China Time Use Survey (CTUS), explores the relationship between parental time and children's well-being and specific influencing factors. Results The more time parents spent with children, the higher their children's well-being will be (coefficient 0.1020, p < 0.01). The life and leisure time parents spent with children promoted children's well-being (coefficient 0.1020, p < 0.01). The life and leisure time the mother spent with children (coefficient 0.1030, p < 0.05) the life and leisure time (coefficient 0.1790, p < 0.05) and the educational interactions time the father spent with children (coefficient 0.3630, p < 0.10) positively affected children's well-being. The influence of the time parents spent with children on children's well-being was heterogeneous based on their children's academic performance. Conclusions Parental accompaniment is an important determinant of children's well-being. Family education, guidance services, and mental health services should be strengthened, and it is necessary to improve the time spent with children and to pay attention to individual differences in children.